PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL PEMBELAJARAN “ROPES” PADA MATERI ALAT-ALAT OPTIK UNTUK KELAS XI SMA - Annisa Mardhatillah; Mitri Irianti; Syahril Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The developed learning media in this research based on ROPES learning model in optics matter for grade XI student of senior high school which consist of learning implementation plan (RPP), student worksheet (LKPD) and students cognitive achievement. This research is aimed to produce learning media based on ROPES Learning model that are valid in optics for XI grade student of senior high school. This is a research and development (R&D) type with 4D development model. The research instrument is RPP validation sheet, LKPD, and the cognitive achievement use descriptive analysis by calculating the validity score for each indicator of learning instrument. Based on the result of validity data analysis, the mean score of RPP validity is 3.48 which can be categorized high. The mean score of LKPD validity is 3,40 wich can be categorized high. The mean score of cognitive achievement validity is 3.39 which is high. The entire score of learning instrument based on ROPES learning model in Optics is 3,44, is declared valid and worth to be used as learning instrument in optics.Key Words: Physics Learning Media, ROPES Learning Model, Optics